SUSTAINABLE EDUCATION: STRATEGIES AND POLICIES FOR DEVELOPING HIGH-IMPACT LEARNING PRACTICES - Loso Judijanto; Muh. Rezky Naim (ADISAM Publisher, 2024)
This study aims to explore strategies and policies that can support the development of high-impact learning practices in the context of continuing education. The research method in this study is the literature review method. The results show that the key to success in implementing sustainable education lies in improving teacher competence, integrating technology in learning, and implementing a flexible and inclusive curriculum. Supportive policies such as the provision of adequate educational infrastructure, support for educational innovation and the establishment of an inclusive learning environment are also important factors in achieving these goals.